Intracellular acidity impedes KCa3.1 activation by Riluzole and SKA-31 - Cozzolino, Marco; Panyi, Gyorgy (Frontiers in Pharmacology, 2024)
The unique microenvironment in tumors inhibits the normal functioning of tumorinfiltrating lymphocytes, leading to immune evasion and cancer progression. Over-activation of KCa3.1 using positive modulators has been proposed to rescue the anti-tumor response. One of the key characteristics of the tumor microenvironment is extracellular acidity. Herein, we analyzed how intraand extracellular pH affects K + currents through KCa3.1 and if the potency of two of its positive modulators, Riluzole and SKA-31, is pH sensitive.Methods: Whole-cell patch-clamp was used to measure KCa3.1 currents either in activated human peripheral lymphocytes or in CHO cells transiently transfected with either the H192A mutant or wildtype hKCa3.1 in combination with T79D-Calmodulin, or with KCa2.2.We found that changes in the intra-and extracellular pH minimally influenced the KCa3.1mediated K + current. Extracellular pH, in the range of 6.0-8.0, does not interfere with the capacity of Riluzole and SKA-31 to robustly activate the K + currents through KCa3.1. Contrariwise, an acidic intracellular solution causes a slow, but irreversible loss of potency of both the activators. Using different protocols of perfusion and depolarization we demonstrated that the loss of potency is strictly time and pH-dependent and that this peculiar effect can be observed with a structurally similar channel KCa2.2. While two different point mutations of both KCa3.1 (H192A) and its associated protein Calmodulin (T79D) do not limit the effect of acidity, increasing the cytosolic Ca 2+ concentration to saturating levels eliminated the loss-of-potency phenotype.Conclusions: Based on our data we conclude that KCa3.1 currents are not sensitive the either the intracellular or the extracellular pH in the physiological and pathophysiological range. However, intracellular acidosis in T cells residing in the tumor microenvironment could hinder the potentiating effect of KCa3.1 positive modulators administered to boost their activity. Further research is warranted both to clarify the molecular interactions between the modulators and KCa3.1 at different intracellular pH conditions and to define whether this loss of potency can be observed in cancer models as well.